Good Health and Wellness: Reflections on Implementing Health Promotion in Indian Country. Issue 6 (November 2021) - Gerber, Colin; Locklear, Sofia; Stewart, Kai; Marshall, LaTisha; Colleen, Gunnar; James, Rosalina
In 2014, the Centers for Disease Control and Prevention (CDC) launched "A Comprehensive Approach to Good Health and Wellness in Indian County" (GHWIC) to promote health and chronic disease prevention in tribal communities while facilitating cross-cultural learning and relationship-building. Through GHWIC, CDC aimed to work with American Indian and Alaska Native communities to identify effective health promotion strategies to address chronic disease disparities. Tribal sovereignty, community context, and consideration of tribal histories (e.g., oppression, genocide, and cultural erasure) are key to health improvement efforts and work with tribes. These elements center experience, knowledge, and self-determination to reclaim good health and wellness as Indigenous peoples see it. The Implementation Reflection Project was a qualitative inquiry composed of one-on-one discussions and small group sessions conducted to explore experiences of CDC staff, national partners, and tribal recipients as they implemented GHWIC program activities. The Project documented observations and recommendations for future tribal health funding efforts and identified best practices for effective partnerships with tribes and tribal organizations. Findings centered around tribal experiences with GHWIC, improved program processes, the importance of relationships, and the effects of internal capacity on implementation. Key suggestions for future work with tribal entities included simplifying and clarifying roles, expectations, and administration requirements, and establishing clear and consistent communication between program partners. The approach CDC used with GHWIC recipients was effective and respectful, but room for growth remains. Potential future collaborators in Indian Country should consider these findings when planning health promotion initiatives.